Monitoring training load and wellness of female footballers transitioning between club and national teams - Brown, G. A.; Massard, T.; Wignell, T.; McCall, A.; Duffield, R. (The Journal of Strength and Conditioning Research, 2023)
This study described the change in training and match internal loads, plus perceptual wellness during the transition between club and national teams (NTs) for female international footballers (soccer). Session count, session rating of perceived exertion (s-RPE), and perceptual wellness data were collected from 42 players from 1 NT between 2019 and 2021 for 7 NT tournaments. Data were collated into 7-day (1 week) microcycles to compare the 2 weeks before the first week of NT (transition in: NT-2, NT-1, NT1); and separately from the final NT week to the next 2 weeks in clubs (transition out: NTFinal, NT+1, NT+2). Data were analyzed using linear mixed-models, with session count, s-RPE or wellness as the outcome variable, week as the fixed effect, player name, and tournament as random effects. Tukey's adjusted post-hoc comparisons and Cohen's d effect sizes (ES) were compared between weeks. Significance level was set at p < 0.05. During the transition into NT, training and total session counts increased (p < 0.0001, ES > 0.67), training s-RPE increased (p = 0.012, ES = 0.35), whereas match count and s-RPE decreased (p < 0.05, ES < -0.34). During the transition out of NT, there were decreases in training session count (p < 0.05, ES < -0.37), match count, and total session count (p < 0.0001, ES < -0.86), and match and total s-RPE (p < 0.0001, ES < -0.63). Perceived wellness was not significantly different throughout (p > 0.05, ES = -0.34 to 0.35). Thus, training and match exposures differ between club and NTs, demonstrating these unique transitional periods require simple and effective load monitoring to inform training and recovery prescription when changing between club and NTs.